Assessment of large-scale circulation and societal impacts of the hydro-geomorphologic event occurred in Portugal, february 1979 - Rebelo, Luis (2017)
Western Iberia is frequently struck by intense mid-latitude cyclones coming from the North Atlantic basin and often impinging extreme weather over large swaths of the Iberian Peninsula (IP). The spatial distribution and characterization of past floods and landslides with important social consequences in Portugal for the period 1865-2015 was performed within the context of the DISASTER project (Zezere et al., 2014). From this database, a major hydro-geomorphologic event was selected, the February 1979, in order to study its atmospheric forcings and to analyze its societal impacts. The February 1979 event is a top ranked event in the DISASTER database regarding the total number of affected (18578), displaced (14322) and evacuated (4244) people in Portugal and in the Tagus basin (7677, 4816 and 2834, respectively). Most of the days considered in this event produced daily precipitation values over or within the 90th-95th percentile of the corresponding long term daily precipitation series (available at high resolution between 1950 and 2008). Most of the event precipitation occurred in days characterized by wet Circulation Weather Types, i.e. cyclonic (C), west (W) or southwest (SW) types, which agrees with the assessment of wet days obtained by Trigo and DaCamara (2000) and Ramos et al. (2014) for the IP domain. Also, throughout this period, the North Atlantic Ocean is crossed several times by narrow and prolonged bands of high moisture concentration, with cores above 9 g/kg, that originate near the Caribbean islands and move towards extratropical latitudes by the influence of southwestern low-level jets of medium or high intensity. These are mostly persistent Atmospheric Rivers (ARs) reaching the western IP coast and affecting most of the month of February until the 16th. Overall, regarding the large-scale circulation, a deep low-pressure system located over the North Atlantic and reaching western IP, allowed for the frequent passage of frontal systems over the territory which was responsible for this precipitation event. In addition, local convective instabilities and strong moisture transport from the Tropical Atlantic produced an extremely intense 15-day precipitation event over western IP, that establishes as the meteorological trigger of the February 1979 Disaster event.